Ski Resorts in Poland and Europe — Selected Issues and Development Options - Żemła, Michał (Turyzm/Tourism, 2004)
Taking part in winter sports often abroad is becoming increasingly popular among Poles. This may be a result of unattractive conditions in terms of price and quality in Polish resorts, and from an excessive national demand over supply causing long queues at ski lifts. The article presents the main issues affecting the functioning and development of ski resorts, quoting examples from West European countries. Particular attention is paid to competition, as well as the role of coordination on the part of local and regional authorities in constructing an offer which would satisfy the needs of a particular segment of this large and varied market.